A multi-objective reactive power optimization strategy for mitigating voltage fluctuation in power network caused by geomagnetic storm - Yang, Pei-Hong; Liu, Lian-Guang; Zheng, Xu-Peng; Han, Xiao-Feng; Feng, Shi-Wei (Advances in mechanical engineering, 2017)
Geomagnetically induced currents through the transformer windings produce biases of transformers, increase transformer reactive power losses, and lead to a significant lack of reactive power support in the power system. As a result, the geomagnetically induced currents cause voltage fluctuations and affect the safe and stable operation of the power network. This study focuses on the problem of multi-objective reactive power optimization strategy to mitigate the negative effects of geomagnetically induced current on the power network. Using the stochastic response surface method, this article establishes a model of the probabilistic power flow calculation, combines a particle swarm optimization algorithm based on the niche chaotic mutation, and sets up a multi-objective reactive power optimization model. The introducing of chaos mutation avoids the result falling into a local optimal solution and improves the global search ability. The geomagnetically induced current–benchmark simulation verified the accuracy and effectiveness of the model and algorithm, and proved that the strategy can effectively reduce the voltage deviation caused by the geomagnetically induced current.